Global stability in a diffusive cholera epidemic model with nonlinear incidence. (January 2021) - Chen, Xiaodan; Cui, Renhao
Abstract: In this paper, we are concerned with a diffusive cholera epidemic model with nonlinear incidence rate. By constructing suitable Lyapunov functionals, we investigate the global stability of the disease free equilibrium and the endemic equilibrium.